Integrating sensory-oriented electrical stimulation with occupation-based, client-centered occupational therapy to support upper limb use after degenerative cervical myelopathy: A case report - Mikari Toki; Takuya Hirose; Sho Maruyama; Hiroki Himeda; Kanta Ohno (British Journal of Occupational Therapy, 2026)
Introduction: Degenerative cervical myelopathy often results in persistent upper limb sensory impairment after surgery, limiting functional hand use despite motor recovery. This case report aimed to describe an occupational therapy intervention integrating sensory-oriented electrical stimulation with occupation-based, client-centered practice to support upper limb use after degenerative cervical myelopathy surgery. Method: This case report describes a woman in her seventies with postoperative degenerative cervical myelopathy who presented with severe bilateral hand numbness, impaired tactile sensation, and difficulty using her left upper limb. Occupational therapy integrated sensory-oriented electrical stimulation with occupation-based practice. Transcutaneous electrical nerve stimulation was applied during upper limb use, combined with finger-equipped electrical stimulation and task-oriented training guided by the Aid for Decision-making in Occupation Choice for Hand. Results: At reassessment, subjective numbness resolved despite residual superficial sensory impairment. The Simple Test for Evaluating Hand Function score improved from 22 to 64 points, and the Quick Disabilities of the Arm, Shoulder and Hand score improved from 88.6 to 20.5. Canadian Occupational Performance Measure scores improved beyond clinically meaningful thresholds, and the patient resumed bilateral hand use. Conclusion: This case suggests that integrating sensory-oriented electrical stimulation with occupation-based occupational therapy may support functional upper limb use in individuals with degenerative cervical myelopathy.